Exploring health literacy pertaining to general wellbeing and chronic disease management among population registered within Primary Healthcare System: A Study protocol - Muslim Abbas Syed; Ahmed Sameer Alnuaimi; Mohamed Ahmed Syed (PLoS ONE, 2025)
Background Evidence suggests that high level of health literacy among patients is associated with high levels of accessibility to healthcare, better understanding consent-to-treat forms, increased compliance to treatment (particularly in taking medication for longstanding chronic diseases), comprehending general healthcare and improved preventive care and early disease detection, proper use of home medical devices from patients and increased capability of accessing the various channels of health information when required. The proposed study aims to assess and capture preferences and perceptions regarding health literacy of population (registered within primary care clinics in state of Qatar) in context to their general wellbeing (physical and mental health) and management of chronic disease conditions. Methods The study design will be mixed methods (include both quantitative and qualitative elements). The HLQ survey will be sent online (text messages) to the population registered with PHCC and to capture service users’ perceptions and preferences pertaining to health literacy channels. The qualitative method will be utilized to gain an in-depth understanding of the various health literacy channels, challenges and barriers pertaining to the implementation of the health literacy strategies from both the healthcare provider and service users’ perspective. The qualitative analysis will be interpreted utilizing the Socioecological Model (SEM). The REPORT statement will be followed during analysis and writing of the study. For the qualitative component we aim to report the results in accordance with ‘Consolidation criteria for reporting qualitative research (COREQ) and ‘Standards for reporting qualitative research ‘(SRQR) guidelines. Results The findings (quantitative and qualitative) will be triangulated to design an evidence-based health literacy framework which can be utilized for service design and re-design to deliver optimal patient centered primary health care services within the country & modelled in similar health care settings geographically. Discussion Evidence generated from the study can increase health literacy levels among service users by modification of health behavior through effective health education. Moreover, increased health literacy levels and improved self-care can lead to improved compliance with treatment leading to effective management of diseases, particularly long-term chronic diseases which are associated with multi-morbidity, polypharmacy and challenges associated side effects of prescribed medications.